Short enantioselective synthesis of the antiepileptic agent, levetiracetam based on proline-catalyzed asymmetric alpha-aminooxylation - Kotkar, Shriram P.; Sudalai, Arumugam (Tetrahedron Letters, 2006)
An efficient enantioselective synthesis of a new antiepileptic drug, levetiracetam is described, in high optical purity (> 99.5% ee), using proline-catalyzed alpha-aminooxylation of n-butyraldehyde as the key step. (c) 2006 Elsevier Ltd. All rights reserved.